Molecular identification of plants: from sequence to species - de Boer, Hugo (Advanced Books, 2022)
This book is for you who are curious about how plants can be identified using DNA: the most powerful source of information to link a plant to a name. This may sound trivial, but it is not. But don't despair in advance: it is doable, mostly fun, and always rewarding. You just need to learn how. Here, you will not only learn how various types of materials containing plant fragments can be identified to species in the lab and how to execute sophisticated computer analyses, but also gain a deeper understanding of the complexities and challenges faced by taxonomy in general, and plant identification in particular, including the lack of comprehensive reference databases. Enforcing strict species concepts onto nature's inherent fluidity doesn't always work, and despite all recent advances in this field it still happens that some plant samples cannot be confidently named. Yet, if this ever happens to you, this initially frustrating insight can also be scientifically revealing, and help you design further experiments.